Quiet time ionospheric variability over Arecibo during sudden stratospheric warming events - Chau Chong Shing, Jorge Luis (2010)
We present observations of the F‐region ionosphere over Arecibo, Puerto Rico (18.34°N, 66.75°W), during the January–February 2008 and January–February 2009 sudden stratospheric warming (SSW) events. For the first period (2008), we have used incoherent scatter radar (ISR) electron density and temperature measurements from the Arecibo Observatory (AO), as well as relative total electron content (TEC) derived from a dual‐frequency GPS receiver. For the second event (2009), during which we observed the largest recorded stratospheric warming, we have used the relative GPS TEC. Our analysis indicates that the ionosphere over Arecibo exhibits perturbations after the SSW, the effects are most visible during the daytime. The strongest signatures are observed in the TEC measurements, represented by large enhancements (with respect to non SSW days), particularly during daytime hours. However, the local time dependence of these enhancements is not the same in the two events. In addition, the data show that our results are consistent with the larger than normal daytime vertical drift differences observed at the magnetic equator over Jicamarca. The electron temperature is also affected during the daytime due to changes in electron density, indicating that the electron temperatures is influenced, indirectly, by changes in planetary wave activity in the lower altitudes.